Effect of green colour on glass quality - M.Al-azzawi, Shatha S. (Iraqi Journal of Physics, 2019)
The study of green colour in glass has a special importance on the glass quality, specially the effect of ferrous oxides content of the limestone. Results obtained that there was a reduction in green colour when different ferrous oxide contents in the limestone were added in glass production, limestone sources from two quarries, and the first contains 0.67% ferrous oxide and the second posses less ferrous oxide. Reduction of green colour showed higher transmittance12% and it could be suggested that reduction of ferrous oxides content in the limestone is of special importance on the optical properties of glass.